2005
DOI: 10.1007/s00125-004-1626-x
|View full text |Cite
|
Sign up to set email alerts
|

Different contribution of class II HLA in fulminant and typical autoimmune type 1 diabetes mellitus

Abstract: Aims/hypothesis: Fulminant type 1 diabetes, which is characterised by a markedly acute onset of diabetes and an absence of islet-related autoantibodies, accounts for 20% of type 1 diabetes in Japan. We aimed to clarify the contribution of the HLA subtype to fulminant type 1 diabetes in Japanese. Methods: We determined the serological subtypes of HLA-A, -DR and -DQ in 115 patients with fulminant type 1 diabetes, 98 patients with typical type 1A diabetes and 190 normal control subjects. Results: The frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(26 citation statements)
references
References 26 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…A few investigators have demonstrated that the frequencies of DR4, DR9, and DR13 haplotypes are significantly increased in acute-onset type 1 diabetic patients [12, 18]. The average age at onset of diabetes was relatively low in previous studies [6,7,8,9,10, 13 ]which did not find a significant susceptibility to DR13 (8.2–30.1 years)[,] except for one report [11] (34.2 years). The average age at onset of diabetes was relatively high in the report of Murao et al [12] (39.3 years), and, as a result, this group reported a susceptibility to DR13.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few investigators have demonstrated that the frequencies of DR4, DR9, and DR13 haplotypes are significantly increased in acute-onset type 1 diabetic patients [12, 18]. The average age at onset of diabetes was relatively low in previous studies [6,7,8,9,10, 13 ]which did not find a significant susceptibility to DR13 (8.2–30.1 years)[,] except for one report [11] (34.2 years). The average age at onset of diabetes was relatively high in the report of Murao et al [12] (39.3 years), and, as a result, this group reported a susceptibility to DR13.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that the DR13 haplotype confers susceptibility to type 1 diabetes, in addition to DR4, DR8, and DR9 haplotypes which confer susceptibility to type 1 diabetes in Japanese patients [5,6,7,8,9,10,11,12,13]. A few investigators have demonstrated that the frequencies of DR4, DR9, and DR13 haplotypes are significantly increased in acute-onset type 1 diabetic patients [12, 18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease may also occur during pregnancy or just after delivery [116, 120]. As a part of the Japanese nationwide survey of FT1DM, it was found that the Class II HLA-DR4-DQ4 (DRB1*04:05-DQB1*04:01) haplotype was significantly more frequent in patients with FT1DM [121]. Interestingly enough, the HLA immunogenetics of pregnancy-associated FT1DM may differ.…”
Section: Type 1 Diabetes With Islet Autoantibodiesmentioning
confidence: 99%